2022
DOI: 10.3390/biomedicines10040871
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Implications of Circulating Circular RNAs in Lung Cancer

Abstract: Circular RNAs (circRNAs) are single-stranded RNAs with a covalently closed-loop structure that increases their stability; thus, they are more advantageous to use as liquid biopsy markers than linear RNAs. circRNAs are thought to be generated by back-splicing of pre-mRNA transcripts, which can be facilitated by reverse complementary sequences in the flanking introns and trans-acting factors, such as splicing regulatory factors and RNA-binding factors. circRNAs function as miRNA sponges, interact with target pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 85 publications
0
2
0
Order By: Relevance
“…circRNA is a new type of noncoding RNA member composed of one or more spliced exons or introns, which has the characteristics of conservation, richness, and tissue specificity, so it may play a special molecular marker role in some diseases (such as tumors) [25]. circRNA can regulate gene expression by alternative splicing, regulating the expression of parental genes, and acting as a scaffold for protein complex assembly and RNA protein interaction and affect the occurrence and development of tumors [26,27]. Previous studies have found that hsa_circ_0061817 is closely related to nonsmall lung adenocarcinoma and has the potential as a biomarker for the prevention and diagnosis of nonsmall lung adenocarcinoma [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…circRNA is a new type of noncoding RNA member composed of one or more spliced exons or introns, which has the characteristics of conservation, richness, and tissue specificity, so it may play a special molecular marker role in some diseases (such as tumors) [25]. circRNA can regulate gene expression by alternative splicing, regulating the expression of parental genes, and acting as a scaffold for protein complex assembly and RNA protein interaction and affect the occurrence and development of tumors [26,27]. Previous studies have found that hsa_circ_0061817 is closely related to nonsmall lung adenocarcinoma and has the potential as a biomarker for the prevention and diagnosis of nonsmall lung adenocarcinoma [28,29].…”
Section: Discussionmentioning
confidence: 99%
“…Circulating cell-free miRNAs (cf-miRNAs) have several advantages as diagnostic biomarkers for NSCLC, including stability, abundance, and specificity. Furthermore, cf-miRNAs can predict drug response by monitoring genetic profiles during treatment, presenting significant potential for personalized therapy [13,14].…”
Section: Introductionmentioning
confidence: 99%